The relationship between maternal knowledge and family support on exclusive breastfeeding: A cross-sectional study - Yustina Oktarida (School of Health Sciences Al-Ma'arif, 2025)
Background Exclusive breastfeeding is vital for optimal infant growth and health, yet its coverage in Indonesia remains suboptimal. Maternal knowledge and family support are key factors influencing breastfeeding success. Objective This study aimed to analyze the relationship between maternal knowledge and family support on exclusive breastfeeding practices. Methods A quantitative study with an analytic survey and cross-sectional design was conducted in the working area of TPMB Ririn Sevda Korini, Ogan Komering Ulu District, in December 2024. A total of 80 respondents were selected using total sampling. Data were collected using a structured questionnaire and analyzed using the Chi-Square test with a 0.05 significance level. Results Most mothers (71.3%) did not practice exclusive breastfeeding. The majority had moderate knowledge (60%) and lacked family support (68.8%). A significant relationship was found between maternal knowledge and family support with exclusive breastfeeding practices (p = 0.000). Conclusion Better maternal knowledge and stronger family support significantly increase the likelihood of exclusive breastfeeding. Breastfeeding promotion interventions should include educational support for mothers and families, workplace-friendly policies, and community-based strategies to foster supportive breastfeeding environments.